Comparison of the Cases in the Department of Forensic Medicine at Ege University as regards the Disability Status Scale and the Disability Scale - Ata, Uğur; Şenol, Ender; Çelik, Cemil (The Bulletin of Legal Medicine, 2021)
Objective: The use of different scales in preparing disability reports results in different rates of disability. Comparing the disability rates measured by the Disability Scale and the Disability Status Scale, this research aims at identiying differences between the scales, thereby indicating various hardships experts encounter. Materials and Method: The cases’ gender, occupation and trauma history as well as the request letters, the injuries related to the event and the examination findings were recorded in case report forms. After calculating each case’s profit loss rate in profession and disability rate, the components that lead to different rates were evaluated. Results: Following trauma, tibial, fibula and vertebral injuries occurred at most, and the most frequent disorders (52%) were found to involve a limitation of movement at a joint and a gait disorder. Since the disorders of almost half of the cases (48.1%) identified with sequela in the Disability Scale do not appear in the A Scale, the discretionary power was enacted. Within the scope of the Disability Status Scale, the discreationary power was employed in 5 cases (3.1%). Average disability ratio of the cases (9.01%) appeared to be significantly lesser (p<0.05) than their average profit loss rate in profession (15.14%). Conclusion: Calculation of different rates for the same sequela in two scales results in unjust treatments. Ensuring conceptual uniformity and updating the two scales in meetings where both legal and forensic experts share their ideas about various challenges in preparing disability reports by declaring their solutions is of significance in issuing reports.